Credit Insurance as a Legal Risk Mitigation Mechanism in Promoting Stability and Soundness in the Banking Industry - Diana R.W. Napitupulu (PT. Anagata Sembagi Education, 2025)
Credit insurance serves as a strategic legal and financial instrument designed to mitigate credit risk in the banking industry. By insuring potential default losses from borrowers, credit insurance operates not only as a risk transfer mechanism but also as a form of legal protection that enhances the resilience and soundness of banks. This paper applies legal protection theory and the theory of the function of law as the main analytical tools to examine how credit insurance contributes to financial stability. Using a normative legal research method, supported by statutory and conceptual approaches, this study finds that the existing regulatory framework in Indonesia while providing a foundation remains insufficient in ensuring effective legal protection for stakeholders. Thus, there is a need for regulatory enhancement, better supervision, and stronger dispute resolution mechanisms to ensure that credit insurance functions optimally in supporting banking health and financial system stability. Indonesia’s regulatory landscape for insurance and banking has evolved significantly, particularly following the enactment of Law No. 40 of 2014 on Insurance and Law No. 21 of 2011 on the Financial Services Authority (OJK). These laws outline the general principles of insurance activities and establish supervisory mechanisms to ensure market integrity. However, specific regulations on credit insurance especially as it pertains to banking risk remain underdeveloped. There is limited guidance on underwriting standards, premium calculation, claims procedures, and dispute resolution mechanisms tailored for credit insurance involving financial institutions. As such, the current framework provides only partial legal certainty and lacks the robustness required to support an effective credit insurance regime in the banking context.